Mechanochemistry and oleochemistry: a green combination for the production of high-value small chemicals - Len, Christophe; Duhan, Vaishaly; Ouyang, Weiyi; Nguyen, Remi; Lochab, Bimlesh (Frontiers in Chemistry, 2023)
Mechanochemistry and oleochemistry and their combination have been known for centuries. Nevertheless, bioeconomy and circular economy concepts is much more recent and has motivated a regain of interest of dedicated research to improve alternative technologies for the valorization of biomass feedstocks. Accordingly, this review paper aims essentially at outlining recent breakthroughs obtained in the field of mechanochemistry and oleochemicals such as triglycerides, fatty acids, and glycerol derivatives. The review discusses advances obtained in the production of small chemicals derived from oils with a brief overview of vegetable oils, mechanochemistry and the use of mechanochemistry for the synthesis of biodiesel, lipidyl-cyclodextrine, dimeric and labelled fatty acids, calcium diglyceroxide, acylglycerols, benzoxazine and solketal. The paper also briefly overviews advances and limits for an industrial application.